Pseudomonas aeruginosa PcrV Enhances the Nitric Oxide-Mediated Tumoricidal Activity of Tumor-Associated Macrophages via a TLR4/PI3K/AKT/mTOR-Glycolysis-Nitric Oxide Circuit - Yu, Hua; Bai, Ying; Qiu, Jing; He, Xiaomei; Xiong, Junzhi; Dai, Qian; Wang, Xingmin; Li, Yuanyuan; Sheng, Halei; Xin, Rong; Jiang, Lu; Li, Qiaoqiao; et al. (Frontiers in Oncology, 2021)
Tumor-associated macrophages (TAMs), which display a tumor-supportive M2 phenotype, are closely related to tumor growth and metastasis. The reprogramming of TAMs toward a tumoricidal M1 profile has emerged as an attractive strategy for cancer immunotherapy. In this study, we found that the intratumoral injection of PcrV protein, a component of the Pseudomonas aeruginosa type three secretion system, suppressed tumor growth and increased apoptosis, inducible nitric oxide synthase (iNOS) expression, and the percentage of M1-polarized TAMs in tumor tissues. Furthermore, the intratumoral injection of PcrV-primed macrophages exerted a similar tumoricidal effect. In vitro analyses revealed that PcrV reeducated TAMs toward an antitumoral M1 phenotype, and augmented their nitric oxide (NO)-mediated cytotoxicity against cancer cells. Mechanistically, we found that these effects were dependent on the activation of Toll-like receptor 4 (TLR4)/myeloid differentiation factor88 (MyD88)-mediated regulation of a PI3K/AKT/mTOR-glycolysis-NO feedback loop via direct interaction with TLR4. Collectively, these results revealed a potential role for PcrV in cancer immunotherapy through the targeting of TAM plasticity.